Physical properties of pyroclastic density currents: relevance, challenges and future directions - Jones, Thomas J.; Beckett, Frances; Bernard, Benjamin; Breard, Eric C. P.; Dioguardi, Fabio; Dufek, Josef; Engwell, Samantha; Eychenne, Julia (Frontiers in Earth Science, 2023)
Pyroclastic density currents (PDCs) are hazardous and destructive phenomena that pose a significant threat to communities living in the proximity of active volcanoes. PDCs are ground-hugging density currents comprised of high temperature mixtures of pyroclasts, lithics, and gas that can propagate kilometres away from their source. The physical properties of the solid particles, such as their grain size distribution, morphology, density, and componentry play a crucial role in determining the dynamics and impact of these flows. Their modification during transport also records the causative physical processes. Understanding these processes from the study of deposits from PDCs and related co-PDC plumes is essential for developing effective hazard assessment and risk management strategies. In this article, we describe the importance and relevance of the physical properties of PDC deposits and provide a perspective on the challenges associated with their measurement and characterization. We also discuss emerging topics and future research directions that are underpinned by the characterization of pyroclasts and their interactions at the micro-scale. We highlight the need to systematically integrate experiments, field observations, and laboratory measurements into numerical modelling approaches for improving our understanding of PDCs.Additionally, we outline a need for the development of standardised protocols and methodologies for the measurement and reporting of physical properties of PDC deposits. This will ensure comparability, reproducibility of results and usability of the data to benchmark future numerical models of PDCs.